The Prognostic Implication of the BRAF V600E Mutation in Papillary Thyroid Cancer in a Chinese Population - Ziheng Ye; Xiaotian Xia; Peipei Xu; Wenfei Liu; Shoufei Wang; Youben Fan; Minggao Guo (International Journal of Endocrinology)
Background. The BRAF V600E mutation is an important genetic event in papillary thyroid cancer (PTC). This study aimed to provide additional information regarding the association of the BRAF V600E mutation with PTC prognosis. Methods. A retrospective single-center study based on a Chinese population was performed to analyze the association of the BRAF V600E mutation with several clinicopathological features. Kaplan–Meier survival curves and Cox proportional hazards regression analysis were applied to implement the survival analysis. Results. The BRAF V600E mutation was present in 1102 (87.7%) of the 1257 patients and was significantly associated with older age, conventional subtype, multifocality, advanced TNM stage, and a reduced prevalence of Hashimoto’s thyroiditis. The Kaplan–Meier survival curves demonstrated that the difference between the BRAF V600E-positive and BRAF V600E-negative groups was significant with a log-rank P-value of 0.048. The Cox proportional hazards regression analysis adjusted HR was 3.731 (95% CI, 1.457 to 9.554). We further demonstrated that larger tumor size (>1 cm), extrathyroidal extension (ETE), and lateral lymph node metastasis (LNM) were associated with a higher probability of PTC recurrence in patients harboring the BRAF V600E mutation. Conclusions. The BRAF V600E mutation remains an independent risk factor for PTC recurrence and may be useful for clinical decisions when it combines with some pathological factors.